The Impact of Behavioral Biases on Individual Investors' ESG Investing - Halminen, Nemo (My University, 2025)
The purpose of this thesis is to examine the impact of behavioral biases on individual investors’ environmental, social and governance (ESG) investing. Furthermore, the thesis seeks to identify some of the biases that occur in such investing and to find out if both herding and biases stemmed from an individual’s beliefs and values impact ESG investments. These biases can cause investors to make irrational financial decisions. ESG investments, gaining a growing amount of attention and adding a non-financial aspect to investing, could be expected to include the aspect of irrationality. The non-rational behavior of investors’ is depicted by behavioral finance. Therefore, it can be expected that some of the biases theorized by behavioral finance occur when individual investors invest in ESG labeled assets. This subject is quite novel and doesn’t have too much academic research on it. As ESG investing gains more and more attention from the investors, the factors leading to investments decisions are important to study. Better understanding of the impact of behavioral biases on the ESG investing of individual investors would provide crucial information of the topic. Existing literature seems to show signs of behavioral biases existing when individual investors invest in ESG assets.

Tämän tutkielman on tarkoitus tutkia käyttäytymisharhojen vaikutuksia yksityissijoittajien ESG-sijoittamiseen. Tutkielma pyrkii tunnistamaan joitakin harhoja, jotka esiintyvät yksityissijoittajien ESG-sijoitustoiminnassa. Työn tarkoitus on myös selvittää, onko sekä laumautumisella, että yksilön arvoihin ja uskomuksiin liittyvillä käyttäytymisharhoilla vaikutusta ESG-sijoittamiseen. Nämä harhat johtavat sijoittajien epärationaalisiin päätöksiin. ESG-sijoittamisen suosio on jatkuvassa kasvussa. Se tuo myös ei-rahallisen näkökannan sijoittamiseen, jonka vuoksi voidaan sen olettaa myös sisältävän irrationaalisen puolen. Sijoittajien epärationalisuutta voidaan kuvata behavioraalisen rahoituksen teorioin, joiden voidaan aiemmin mainitun perusteella olettaa olevan osa yksityissijoittajien ESG-sijoituksia. Aiheena behavioraalisen rahoituksen tutkiminen osana ESG-sijoituksia on melko uusi, joten sitä ei ole tutkittu paljon. ESG-sijoittamisen suosion kasvaessa, on tärkeää oppia tuntemaan sijoituspäätöksiin johtavat tekijät. Käyttäytymishäiriöiden ymmärtäminen osana yksityissijoittajien ESG-sijoituksia tuo tärkeää tietoa aiheeseen liittyen. Olemassa oleva kirjallisuus näyttäisi viittaavan siihen, että käyttäytymishäiriöitä esiintyy osana yksityissijoittajien ESG-sijoitustoimintaa.
Keywords: investors; decision making; behaviour; responsible investing; behavioural economics; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Finance